Identification of Key Gene Networks Associated With Cell Wall Components Leading to Flesh Firmness in Watermelon - Anees, Muhammad; Gao, Lei; Umer, Muhammad Jawad; Yuan, Pingli; Zhu, Hongju; Lu, Xuqiang; He, Nan; Gong, Chengsheng; Kaseb, Mohamed Omar; Zhao, Shengjie; Liu, Wenge (Frontiers in Plant Science, 2021)
Flesh firmness of watermelon is an important quality trait for fruit commercial values including fruit storability, transportability and shelf life. To date, knowledge on the gene networks underlying this trait is still limited. Herein, we used weighted genes coexpression network analysis based on correlation and the association of cell wall contents with transcriptome profiles of two materials, a near isogeneic line (HWF) with high flesh firmness and inbred line (203Z) with low flesh firmness to identify the gene-networks responsible for changes in fruit flesh firmness. We identified three gene-networks/modules, containing 354 genes highly correlated with water-soluble pectin, ionic bond pectin, cellulose, hemicellulose and protopectin. Within these modules, based on intramodular significance and RT-qPCR, eight genes involved in cell wall biosynthesis and ethylene pathway are identified. Two genes (Cla012351 and Cla004251) from darkgreen module, correlated with hemicellulose (r²=0.83) and protopectin (r² = 0.81), three genes (Cla007092, Cla004119, Cla018816) from grey60 module, correlated with cellulose (r² = 0.85), hemicellulose (r² = 0.8) and protopectin (r² = 0.8), and three genes (Cla004120, Cla009966, Cla006648) from lightcyan module, correlated with water- soluble pectin (r² = 0.91), ionic-bond pectin (r² = 0.95), cellulose (r² = 0.93) , hemicellulose ( r²= 0.9 ) and protopectin ( r² = 0.92 ) are identified. Annotation and phylogenetic history of genes validates their relatedness with pectin esterase, xyloglucan endoglcosyltransferase, glycosyltransferase, cellulose synthase and ethylene response element (ERF). This study generated important insights of biosynthesis of cell wall structure and ethylene signaling transduction pathway of watermelon.